Encyclopedia of philosophy - Borchert, Donald M. 1934- (Gale virtual reference library, 2005)
English-language reference source for philosophy," has been the cornerstone of the philosophy reference shelf. Lauded for its clear and accessible presentation of wide-ranging philosophical subjects, the Encyclopedia has earned its place as a first-stop resource for general readers, students and educators.